ENTROPY, TRANSINFORMATION AND WORD DISTRIBUTION OF INFORMATION-CARRYING SEQUENCES - Ebeling, Werner; Pöschel, Thorsten; Albrecht, Karl-Friedrich (International Journal of Bifurcation and Chaos, 1995)
We investigate correlations in information carriers, e.g. texts and pieces of music, which are represented by strings of letters. For information carrying strings generated by one source (i.e. a novel or a piece of music) we find correlations on many length scales. The word distribution, the higher order entropy and the transinformation are calculated. The analogy to strings generated through symbolic dynamics by nonlinear systems in critical states is discussed.<br